## Trending News

# Do British women date? And what is the appropriate wording for asking a British woman out on a date? ?

I am an American who just went out on a couple of dates with a British woman... or so I thought. About a week after what I thought were two very successful dinner dates at nice restaurants she tells me she just wants to be friends and that we never actually dated. She then claims "British women do not date" and because I did not use the word "date" when I asked her out to dinner this made it clear in British culture that it was just dinner between two friends. When I initially asked her out my exact words were: "I'd like to take you out to dinner." For the record, I paid for dinner both times and we even had a discussion that British and American customs differ on this point. I distinctly remember her telling me that she was well aware of this difference because she used to have an American boyfriend. Is it true that British women do not date? Is this an genuine cultural misunderstanding? Or is this woman just a coward who chose a pathetic way of dumping a guy?

### 2 Answers

- somersetLv 44 years ago
(4m-7)/2=10 Multiply via 2 to get rid of your denominator.(you're "undoing" the branch via multiplying. 2 x (4m-7)/2= 10 x 2 4m - 7 = 20 upload 7 to the two factors of the equation 4m - 7 + 7 = 20 + 7 4m = 27 Divide via 4 m = 27/4 (or 6 3/4) examine: replace m with 27/4 [4 (27/4) -7 / 2=10 27 - 7 / 2 = 10 20/2 = 10 10 = 10 ... the respond tests out, this is in basic terms right. (3x+a million)/5= -3 Multiply via 5 5 x (3x + a million)/5 = -3 x 5 3x + a million = - 15 Subtract a million from the two factors 3x + a million - a million = -15 -a million 3x = -sixteen Divide via 3 x = -sixteen/3 examine: [3 (-sixteen/3) +a million] / 5= -3 (- 40 8/3 + a million)/5 = -3 (-sixteen + a million)/5 = -3 -15/5 = -3 -3 = -3 5n-2 = n+18 upload 2 to the two factors of the equation 5n - 2 + 2 = n +18+2 5n = n + 20 Subtract n from the two factors 5n - n = n - n + 20 4n = 20 Divide via 4 n = 5 examine: 5(5) - 2 = 5 +18 25 - 2 = 23 23 = 23 -3 - 6x=27+4x upload 3 to the two factors -3 +3 - 6x = 27 +3 + 4x -6x = 30 + 4x Subtract 4x from the two factors -6x -4x = 30 +4x -4x -10x = 30 Divide via -10 x = -3 examine: -3 - [6 (-3)]=27+[4(-3)] -3 - (-18) = 27 + (-12) -3 + 18 = 27 - 12 15 = 15 24 - 5e=e same as a results of fact the above. start up via including 5e ... finally finally end up answer is e = 4 5(x+4)=32 Distribute/muliply via 5 to end left fringe of the equation 5x + 20 = 32 Subtract 20 from the two factors 5x = 12 Divide via 5 x = 12/5 examine: 5 (12/5 + 4) = 32 12 + 20 = 32 32=32 4(15-x)=20-9x Multiply the 4 via first 60 - 4x = 20 - 9x upload 4x to the two factors 60 = 20 - 5x Subtract 20 40 = - 5x Divide via -5 -8 = x examine: 4[15 - (-8)=20 - 9(-8) 4 (15 + 8) = 20 - (-seventy two) 4 (23) = 20 + seventy two ninety two = ninety two 10 - 3(m-2) = 8 Multiply via -3 10 - (3m - 6) = 8 10 - 3m + 6 = 8 sixteen - 3m = 8 Subtract sixteen from the two factors - 3m = -8 Divide via -3 m = - 8/-3 = 8/3 (or 2 2/3) examine: 10 - 3 [(8/3 - 2] = 8 10 - [8 - 6] = 8 10 - (2) = 8 8 = 8 My 2 ultimate algebra information: a million) Algebra is like untying a knot. "Undo" one operation with the alternative operation. "Undo" branch with multiplication and addition with subtraction (and vice versa). finally you will get to a factor the place you may isolate your unknown on one fringe of the equation and remedy for it. 2nd tip, continuously examine your answer. each and every so often you're able to do something rather stupid incorrect and you will seize it. stable success!

- Anonymous1 decade ago
Of course they do.